El acoso escolar y sus efectos en el aprendizaje de los estudiantes de Educación General Básica - Sandoval Chávez, María de Lourdes (2022)
Violence in the school environment has existed and has been evidenced by the use of punishments and violent methods about the teaching and learning processes. In Ecuador lately, a different type of violence has become visible at school: peer violence. There are not many studies on this issue that have been carried out in the country and it has not been fully addressed. The main forms of bullying among peers in schools have been identified, which is why this research aims to describe the situation of bullying as an influencing factor in the learning process and educational quality of students in the middle school sub-level. Individual of Basic Education Child Dreams..........